Interprofessional Collaborative Practice and Health Workers Retention at Remote Primary Health Care: Case Study from Nusantara Sehat Team-based Program - Soewondo, Prastuti; Pujisubekti, Retno; Prastyani, Ade Widyati; Rahmayanti, Nurul Maretia (Kesmas, 2022)
The Nusantara Sehat Team (NST), established in 2015 and consist of multi-professional health workers, implemented to provide comprehensive services at remote primary health cares (PHCs) for two years. This study aimed to explore how the NST leverages the Interprofessional Collaboration (IPC) and its impact on the future career prospects of health workers. Using a qualitative approach, the information was gathered from 48 informants drawn from the current 30 NST recruits and 18 alumni through semi-structured interviews. Of these 48, 20 were clinical practitioners, while the rest were non-clinical health workers. The findings revealed several challenges in promoting collaborative practice, including the community's high demand for curative services, the unclear division of tasks among the NST and local PHC staff, and inadequate health facility support. The curriculum of IPC was yet to be included in the pre-service education and in-service training before NST, allowing the staff to enter the workplace and collaborate, especially in the backward areas. The institutional support through macro and meso policies has yet to enable collaborative-practice ready workers adequately. Other factors such as personal values, family expectations, gender roles, and career sustainability also affected the retention of personnel in the NST.